PrEP knowledge, attitudes, and perceived barriers to access among American Indian/Alaska Native people in the US: Results from an online survey - Sarah T. Roberts; Sarah M. Hatcher; Erica N. Browne; Brigg Reilley; Matthew Bensen; Andrew Freeman; Bob Henne; Ashley Hoover; Monica M. Desjardins; Jessica Leston (PLoS ONE, 2025)
Introduction Compared to non-Indigenous communities, American Indian/Alaska Native (AI/AN) people are inequitably impacted by HIV, yet few data are available on barriers to pre-exposure prophylaxis (PrEP) use in this population. This study sought to examine PrEP knowledge, attitudes, and perceived barriers to use among AI/AN people in the United States. Methods A cross-sectional, online survey was administered from January-May 2023 to respondents ≥ 16 years of age who identified as AI/AN. The survey assessed sociodemographic characteristics, PrEP knowledge, attitudes towards PrEP, and experiences with and barriers to PrEP use. Sociodemographic correlates of PrEP knowledge and attitudes were identified using bivariable and multivariable regression models. Results The survey enrolled 403 participants and 354 (87.8%) completed all questions. Respondents had relatively low PrEP knowledge (mean score 4.0 of 9, standard deviation [SD] 3.0). Few (7%) had ever used PrEP. Mean scores on the stigma scales were 2.1 of 5 for stigmatizing PrEP attitudes (SD 0.7), 2.4 of 5 for anticipated stigma (SD 0.56), and 3.0 of 5 for perceived stigma (SD 0.38). Among non-users, 43.1% were not sure if they would be able to get a PrEP prescription if they desired, and 2.7% believed they would not be able to get one. The most common perceived barriers were not knowing where to get PrEP (54.7%) and concerns around discomfort, judgement, and privacy at the health facility (27.3%). In adjusted models, living on tribal/reservation lands was significantly associated with lower PrEP knowledge, higher stigmatizing attitudes, and higher anticipated stigma, and lower PrEP knowledge was associated with higher stigmatizing attitudes and anticipated stigma. Age, gender identity, sexual orientation, urban residence, and strength of connection to indigenous culture were also significantly correlated with one or more outcomes. Conclusions Our findings underscore the need for widespread sensitization about PrEP in Indigenous communities and for strategies to improve PrEP access and reduce stigma from providers and community members.